Teachers' Experience of Professional Development in Differentiated Teaching in an English Language Center - Rohmadhani, Annisa; Suryati, Nunung; Wulyani, Anik Nunuk (Language Circle: Journal of Language and Literature, 2025)
Teacher professional development (TPD) is crucial to prepare teachers in addressing classroom diversity and learning needs through differentiated teaching. This study aims to explore teachers’ opinions of their TPD experience related to differentiated teaching. Using a descriptive quantitative research method, the data were collected through structured questionnaires focusing on Desimone’s (2009) five domains of TPD: content focus, active learning, coherence, duration, and collective participation. A total of 24 respondents participated, discovering several variations of engagement level in TPD programs and differing points of view on their relevance and practicality. Results show that many teachers agreed the programs were moderately effective as the institution gave support for TPD; however, the participation was inconsistent. The study contributes to explaining how TPD prepares them to accommodate learners’ needs by implementing differentiated teaching in class. This offers insights for curriculum developers, education policymakers, and institutional leaders who seek ways to improve teachers’ capacity through targeted professional development, specifically in differentiated teaching.